The protective roles of allicin on type 1 diabetes mellitus through AMPK/mTOR mediated autophagy pathway - Qian, Rengcheng; Chen, Huihui; Lin, Hongzhou; Jiang, Yalan; He, Pingping; Ding, Yinjuan; Wu, Huilan; Peng, Yongmiao; Wang, Lingfei; Chen, Congde; Wang, Dexuan; Ji, Weiping; et al. (Frontiers in Pharmacology, 2023)
Type 1 diabetes mellitus (T1DM) is one of the most common endocrine and metabolic diseases in children. Pancreatic β cells are thought to be critical cells involved in the progression of T1DM, and their injury would directly lead to impaired insulin secretion. The aim of this study was to investigate the protective effects of allicin on pancreatic β cell injury and elucidate the underlying mechanism. The streptozotocin (STZ)-induced mouse T1DM model in vivo and STZ-induced pancreatic β cell Min6 model in vitro were used to explore the effects of allicin on T1DM. The experiments include fasting blood glucose test, oral glucose tolerance detection, HE staining, immunohistochemistry, immunofluorescence, TUNEL staining, western blot, real-time quantitative PCR (RT-qPCR), and flow cytometry. The results showed that allicin could significantly decrease blood glucose level, improve islet structure and insulin expression, and inhibit apoptosis to reduce STZ-induced pancreatic β cell injury and loss through activating AMPK/mTOR mediated autophagy pathway. In summary, our study showed that allicin treatment significantly reduced STZ-induced T1DM progression, suggesting that allicin may be a potential therapy option for T1DM patients.